Panaroma of microglia in traumatic brain injury: a bibliometric analysis and visualization study during 2000–2023 - Zhang, Yuhang; Deng, Tingzhen; Ding, Xiao; Ma, Xingyuan; Wang, Yatao; Yang, Haijun; Ding, Ruiwen; Wang, Dawen; Li, Haotian; Zheng, Maohua (Frontiers in Cellular Neuroscience, 2024)
Background Traumatic brain injury (TBI) is a critical global health concern characterized by elevated rates of both morbidity and mortality. The pathological and physiological changes after TBI are closely related to microglia. Microglia, the primary immune cells in the brain, are closely linked to the mechanisms and treatment of TBI. With increasing research in this area, this study employs bibliometric analysis to identify current research hotspots and predict future trends. Objective We decided to perform a bibliometric analysis to provide a comprehensive overview of the advancements in microglia research related to traumatic brain injury. We aim to offer researchers insights into current trends and future research directions. Method We collected all articles and reviews related to microglia and traumatic brain injury published between 2000 and 2023 from the Web of Science Core Collection. These records were analyzed using VOSviewer, CiteSpace, and the R package “bibliometrix”. Results We retrieved 665 publications from 25 countries, with the majority contributed by the United States and China. The number of publications on traumatic brain injury and microglia has been steadily increasing each year. Our analysis highlighted the Journal of Neurotrauma and the Journal of Neuroinflammation as the most influential journals in this field. Alan I. Faden and David J. Loane are recognized as leading contributors. Keyword analysis indicates that neuroinflammation, microglial polarization, and neurodegenerative diseases are pivotal areas for future research. Conclusion In recent years, research on TBI-related microglia has proliferated, with current studies primarily focusing on microglial involvement in neuroinflammation, neurodegenerative changes, and microglial polarization following TBI. Since neuroinflammation and neurodegeneration are two hallmark features of TBI, targeting microglia in TBI treatment may become a central focus for future research.